Chronic airway inflammation in Drosophila lacking the A20-like protein Trabid - Bossen, Judith; Knop, Mirjam; Niu, Xiao; Thiedmann, Marcus; Prange, Ruben; Tahanzadeh, Navid; Franzenburg, Sören; Bruchhaus, Iris; Heine, Holger; Roeder, Thomas (Frontiers in Immunology, 2025)
BackgroundLong-term disruption of epithelial immune homeostasis plays a key role in the development and persistence of chronic lung diseases. The regulation of immune pathways, especially the NF-kB pathway, is crucial for maintaining this balance. A20 (TNFAIP3) acts as an inhibitor of the NF-kB pathway and has been linked to chronic lung disease.MethodsWe investigated the functional role of A20 by studying its Drosophila ortholog, Trabid. trabid-deficient flies were analyzed for immune response activation, susceptibility to various airborne stressors (dehydration, chronic cigarette smoke, and hypoxia), and their cellular adaptation to hypoxia in the tracheal system.Resultstrabid-deficient Drosophila exhibited chronically activated immune responses in airway epithelial cells. These animals showed markedly increased sensitivity to dehydration, cigarette smoke, and hypoxic stress. Moreover, the plastic (adaptive) response of terminal tracheal cells to hypoxia, normally present in wild-type animals, was lost.ConclusionLoss of A20/Trabid leads to disease-associated phenotypes resulting not only from heightened epithelial immune activity, but also from a profound reduction in the organism’s ability to withstand environmental stresses. This highlights the dual importance of immune regulation and stress resistance in epithelial health and chronic lung disease.